Les générations au travail : des cultures différentes ou un collectif qui se méconnaît ? Le cas des techniciens d’Edf - Jérémie Rosanvallon (La Nouvelle Revue du Travail)
Between the massive number of people retiring and arrival of young employees deemed to have their own specific culture, generational replacement has become a growing problem in many businesses today. Above and beyond media and management discourse, the real question is the meaning of this succession process and to what extent it is actually happening, i.e. whether there is justification for analysis to be couched in these terms. The article uses the example of Edf technicians to show that the opposition between generations sometimes derives less from real cultural divergence and more from corporate transitions and the conditions of inter-individual exchange. Distinctive generational groups may exist but they are more the product of interactions between colleagues and professional changes than of individuals' specific characteristics. Interviewed just as Edf's electricity markets were being opened up to competition, the company's older technicians emphasized the cultural and professional gap separating them from their younger counterparts. In their view, the two groups had not received the same training, had different values and felt differently about the company. At the same time, the survey revealed that the younger technicians were more like their elders than they might first seem. In reality, criticisms of the younger technicians reflected their colleagues' unhappiness with the transformations affecting the company, something they associated with the new arrivals. This amalgamation stemmed from the fact that the new generation was a clearly identifiable cohort, given the way that the wave of recruitments more or less coincided with the announcement that Edf's core markets were being opened up to competition. Another factor was the progressive shift in technicians' concrete conditions of exchange , culminating in their becoming increasingly isolated from one another. Older workers did not really know their younger colleagues and were therefore more likely to misrepresent them.